DELINEASI POTENSI BENTONIT MENGGUNAKAN METODA GEOLISTRIK DI DESA SEKARWANGI, KECAMATAN CURUGBITUNG, KABUPATEN LEBAK, PROVINSI BANTEN: DELINEATION OF BENTONITE POTENTIAL USING GEOELECTRIC METHOD IN SEKARWANGI VILLAGE, CURUGBITUNG DISTRICT, LEBAK REGENCY, BANTEN - Ade Ihsanudin; Mega Fatimah Rosana; Johanes Hutabarat (Buletin Sumber Daya Geologi, 2023)
Bentonite is an abundant mineral resource in Indonesia, based on data from the Center for Coal and Geothermal Mineral Resources (PSDMBP) in 2021 the measured resource of bentonite is 3,299,072,992.75 tons and has not been utilized optimally. Sekarwangi Village has bentonite resources, based on that the purpose of this research was conducted to find out the potential and types of bentonite found in the Sekarwangi area so that it can be put to good use. Sekarwangi Village is located in Curugbitung District, Lebak Regency, Banten Province, Indonesia. This research is divided into two stages, namely field activities and laboratory activities. Field activities include geological observations and geoelectric measurements. Laboratory activities are testing the geochemical content of rocks in the form of XRF (X-ray Fluorescence) and XRD (X-Ray Diffraction)analysis. The result shows that the rocks are composed of volcanic deposits, one of which is tuff. Based on the results of chemical analysis, bentonite in the study area is classified in the Ca-Bentonite category. Potential bentonite layer can be found at the depth of 1.27 - 40.24m. Bentonite has thickness ranging from 9.6m to 34.61m. The resistivity value ranges from 0.09 - 9.69 ohm/m.